Turning liberal: Legislators’ individual preferences and the regulation of pre-implantation genetic diagnosis in Switzerland - Baumann, Markus (Swiss political science review, 2018)
Most policy-making decisions taken in parliamentary democracies are essentially matters of party competition. Yet, in some policies, the linkage function of political parties is limited by purpose, which is frequently the case in free votes with a morality dimension. This has led to a debate in the literature on the determinants of Legislators’ preferences in free votes. The present research note adds to this debate by analyzing the parliamentary procedure to regulate pre-implantation genetic diagnosis (PGD) in Switzerland. By assessing whether and to what degree MPs based their decision on their personal characteristics and on the preferences of their constituents, the contribution shows that not only are MPs’ voting decisions determined by these individual level factors, but also that these factors have detectable effects on the legislative outcome.